Estimation and Sensitivity of Carbon Storage in Permafrost of North‐Eastern Yakutia. (9th January 2017) - Shmelev, Denis; Veremeeva, Alexandra; Kraev, Gleb; Kholodov, Alexander; Spencer, Robert G. M.; Walker, Wayne S.; Rivkina, Elizaveta
Abstract: Organic carbon derived from permafrost can provide a substrate for greenhouse gas production where the buried carbon pool thaws and mobilizes into biogeochemical cycles. Much attention has focused on the permafrost carbon of the Yedoma region of Siberia due to the wide distribution of organic and ice‐rich deposits. Here, we present a new estimation of carbon storage in the upper 25 m of permafrost in north‐eastern Yakutia based on a novel database of total carbon (TC) content, bulk density and ice content of permafrost, and a new map of Quaternary deposits derived from drilling data. The stratigraphic units contain 0.6–2.1% TC, with the highest concentrations in the Holocene cover layer and Late Pleistocene Yedoma superhorizon. The largest carbon pool is found in the Pliocene/Middle Pleistocene Olyor superhorizon. The TC pool of Yedoma is estimated to be 1.5–2 times less than that calculated previously. The TC pool of the study area is 31.2 ± 15.2 Pg C spread across 88 000 km 2, with a mean specific carbon content of approximately 14.3 kg C m −3 . Carbon storage is estimated excluding the ice‐wedge volume and, due to the limited data for Yedoma and Alas deposits, we present a maximal assessment of the carbon pool for the Yedoma region. Refinement of the size of the Yedoma TC pool is critical for quantifying the scale of permafrost feedback to the carbon cycle. Copyright © 2017 John Wiley & Sons, Ltd.